2014
DOI: 10.1016/j.jtcvs.2014.08.021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bilateral internal mammary arteries on short- and long-term outcomes: A propensity score matching in accordance with current recommendations

Abstract: When compared with SIMA grafting, BIMA use did not increase operative morbidity and mortality and was associated with a better long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…In our analysis, the rate of mediastinitis or sternal dehiscence was 2.8% in BIMA patients versus 1.8% in SIMA patients; this difference did not achieve statistical significance. Current literature on the association between multiarterial grafting and sternal wound complications is mixed, with some demonstrating no association and others showing a slightly increased risk [19][20][21]. A recent literature review by Dai and colleagues showed that whereas BIMA grafting resulted in an increase in sternal wound infections, the associated risk was blunted when the IMA was harvested in a skeletonized fashion [19].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, the rate of mediastinitis or sternal dehiscence was 2.8% in BIMA patients versus 1.8% in SIMA patients; this difference did not achieve statistical significance. Current literature on the association between multiarterial grafting and sternal wound complications is mixed, with some demonstrating no association and others showing a slightly increased risk [19][20][21]. A recent literature review by Dai and colleagues showed that whereas BIMA grafting resulted in an increase in sternal wound infections, the associated risk was blunted when the IMA was harvested in a skeletonized fashion [19].…”
Section: Commentmentioning
confidence: 99%
“…Multiple retrospective analyses have demonstrated that patients undergoing CABG with bilateral internal mammary artery (BIMA) grafting have significantly improved survival and freedom from repeat revascularization when compared with patients receiving a single internal mammary artery (SIMA) [15][16][17][18]. The observed clinical benefits of a BIMA approach have been tempered, however, by concerns over the risk of sternal wound complications among the obese and diabetics [19][20][21]. Moreover, in the recently published 5-year interim analysis of the Arterial Revascularization Trial (ART), Taggart and colleagues reported a significant increase risk of sternal wound complications among BIMA patients [22].…”
mentioning
confidence: 99%
“…A second arterial conduit to a non‐LAD target has less potential to impact on overall survival than the single left internal thoracic artery to the LAD. Solid evidence suggests, in fact, that in coronary artery bypass surgery, patient survival is mainly determined by the status of the LAD and that grafts to non‐LAD vessels are more likely to affect other cardiac end points (myocardial infarction, angina recurrence, and need for revascularization), but not overall survival . The LAD also can provide collaterals to other coronaries (commonly the right coronary); a persistently patent internal thoracic artery graft to the LAD can therefore supply not only the anterior wall, but, through collaterals, viable myocardium in other territories.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is a potential future issue since there are growing burden of published studies showing better long-term survival in patients receiving bilateral ITA compared with s ingle ITA grafting [53][54][55][56].…”
Section: Sex-specific Outcomes Following Cabgmentioning
confidence: 99%